Teachers' perception of inclusive teaching practices for students with severe permanent disabilities / Percepción del profesorado sobre prácticas docentes inclusivas en alumnado con discapacidades graves y permanentes. Issue 3 (3rd July 2019) - Colmenero, María-Jesús; Pegalajar, María-Carmen; Pantoja, Antonio
Abstract: This study examines the perceptions of teachers in special education schools regarding the use of inclusive practices for students with severe permanent disabilities. The research was performed in Andalusia (Spain), using surveys as the main data collection method. To this end, a specific scale was designed and validated, and surveys were filled out by 428 teachers who worked in one of the 59 special education schools in the region. The data analysis shows that the teachers had positive perceptions of the use of inclusive teaching practices; there were significant relationships between variables related to the type of school, as well as gender, age and teaching experience.